Photocatalytic degradation of municipal wastewater and brilliant blue dye using hydrothermally synthesized surface-modified silver-doped ZnO designer particles - Parvin T. (2014)
Photocatalytic degradation of local municipal wastewater and brilliant blue FCF dye were investigated using silver-doped ZnO designer particles. The silver-doped ZnO designer particles were synthesized under mild hydrothermal conditions (T = 150-250° C, P = autogeneous, experimental duration = 16-24h) in the presence of surface modifiers. The resultant products were characterized using powder XRD, FTIR, Zeta potential, and SEM. Various parameters including catalyst amount, light source, pH, and photocatalytic time duration were studied to find out their effects on photodegradation efficiency with respect to municipal wastewater and brilliant blue dye. The effect of these parameters was evaluated using chemical oxygen demand (COD) and transmittance analyses. The photodegradation results showed that the surface-modified silver-doped ZnO designer particles had higher efficiency compared to the reagent-grade ZnO in photodegradation of municipal wastewater and brilliant blue dye. Copyright © 2012 Tabasom Parvin et al.